2009
DOI: 10.1203/pdr.0b013e3181b1bd05
|View full text |Cite
|
Sign up to set email alerts
|

The −174GG Interleukin-6 Genotype Is Protective From Retinopathy and Nephropathy in Juvenile Onset Type 1 Diabetes Mellitus

Abstract: ABSTRACT:The aim of our study was to determine an association between the Ϫ174GϾC IL-6 polymorphism (rs1800795) and occurrence of retinopathy and nephropathy in type 1 diabetes mellitus (T1DM) patients. Two hundred ten children/adolescents with longstanding T1DM (16.5 Ϯ 3.8 y; with diabetes duration of 8.4 Ϯ 3.0 y) were enrolled into the study. A group of 170 healthy young (16.9 Ϯ 5.2 y) sex-matched volunteers was qualified as the control. The IL-6 polymorphism was genotyped with the PCR-RFLP method. Serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…In addition, the time since diagnosis might not, also, be a confounding factor within this analysis, because no significant difference was found between the CC and GG+GC carriers. The relationship between the CC genotype and kidney injury was also reported by Mysliwska et al , in which T1DM patients carrying the GG genotype were shown to be protected from late diabetic complications, including nephropathy. Because IL‐6 induces several alterations in the kidney, this polymorphism is thought to contribute to renal impairment in T1DM.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In addition, the time since diagnosis might not, also, be a confounding factor within this analysis, because no significant difference was found between the CC and GG+GC carriers. The relationship between the CC genotype and kidney injury was also reported by Mysliwska et al , in which T1DM patients carrying the GG genotype were shown to be protected from late diabetic complications, including nephropathy. Because IL‐6 induces several alterations in the kidney, this polymorphism is thought to contribute to renal impairment in T1DM.…”
Section: Discussionsupporting
confidence: 66%
“…To the best of our knowledge, the present study is the first to evaluate the association of this polymorphism with T1DM in a group of Brazilian patients. The association between T1DM and the C allele and CC genotype for IL6 ‐174G>C was also shown in Polish , British , and Danish patients. In contrast, another British study found that the GG genotype was more frequent in T1DM patients compared with control subjects , and no association was identified in a meta‐analysis including mainly Caucasian patients .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A link to elevated DR risk has also been reported for concomitant polymorphisms in genes for enzymes involved in folate metabolism 84. Conversely, a polymorphism in the gene for interleukin 6 in adolescents with type 1 diabetes has been found to have a protective effect 85. Further studies will likely permit a better delineation of the metabolic pathways related, either positively or negatively, to DR development in paediatric populations with diabetes.…”
Section: Risk Factorsmentioning
confidence: 96%
“…Similarly, Tsiavou et al (2004) did not find an association of IL-6 -174G>C (rs1800795) with LADA (Latent Autoimmune Diabetes of the Adult). Additionally, some studies suggest that the -174GG genotype is protective against early T1D onset; however, this protection may be lost later in life (Jahromi et al, 2000;Gillespie et al, 2005;Hermann et al, 2005;Mysliwska et al, 2009).…”
Section: Discussionmentioning
confidence: 99%